PENGARUH KUALITAS PELAYANAN, HARGA, PROMOSI, KEAMANAN TRANSAKSI, DAN LOYALITAS PERUSAHAAN TERHADAP PENGAMBILAN KEPUTUSAN PEMBELIAN TIKET PESAWAT ONLINE PADA APLIKASI TRAVELOKA (Jurnal Riset Manajemen Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha Program Magister Manajemen, 2021)
Based on the t test results, the quality of service has a significant effect on purchasing decisions with a significance value of 0.008 smaller than 0.05 (0.008 less than 0.05), meaning the quality of service has a significant influence on the purchase decision. The price significantly affects the purchase decision with a significance value of 0.000 smaller than 0.05 (0.000 less than 0.05), which means that the price has a significant influence on the purchase decision. Promotion significantly affects the purchase decision with a significance value of 0.047 smaller than 0.05 (0.047 less than 0.05), meaning the promotion has a significant effect on the purchase decision. Transaction security significantly affects purchase decisions with a significance value of 0.017 less than 0.05 (0.017 less than 0.05), meaning transaction security has a significant effect on the purchase decision. Company loyalty significantly affects the purchase decision with a significance value of 0.037 smaller than 0.05 (0.037 less than 0.05), meaning company loyalty has a significant influence on purchasing decisions.
Keywords: service quality; price; promotion; transaction security; corporate loyalty; purchase decision